Design and Biomimicry: A Review of Interconnections and Creative Potentials - Alice Araujo Marques de Sá; Dianne Magalhães Viana (Biomimetics, 2023)
The study and application of biological knowledge favor the creation of innovative projects in several areas, so it is necessary to better understand the use of these resources specifically in the field of design. Thus, a systematic review was undertaken to identify, describe, and analyze the contributions of biomimicry to design. For this purpose, the integrative systematic review model, called the Theory of Consolidated Meta-Analytical Approach, was used, carrying out a search on the Web of Science with the descriptors “design” and “biomimicry”. For the period from 1991 to 2021, 196 publications were retrieved. The results were organized according to areas of knowledge, countries, journals, institutions, authors, and years. Citation, co-citation, and bibliographic coupling analyses were also performed. The investigation highlighted the following research emphases: the conception of products, buildings, and environments; the exploration of natural structures and systems to create materials and technologies; the use of biomimetic creative tools in product design; and projects focused on saving resources and implementing sustainability. It was noted that there was a tendency for authors to adopt a problem-based approach. It was concluded that the study of biomimicry can stimulate the development of multiple skills in design, improving creativity, and enhancing the potential integration of sustainability into production cycles.